Theoretical Study on Spectroscopy and Molecular Constants of the Ground and Low-Lying Excited States of GeO Molecule (Journal of Atomic and Molecular Sciences, 2021)
The potential energy curves (PECs) of $X¹Σ^+,$ $a'³Σ^+,$ $a³Π,$ $A¹Π$ states for GeOmolecule are calculated by the multireference configuration interaction method (MRCI)and MRCI with the Davidson's corrections (MRCI+Q) with aug-cc-pVTZ basis set. Allthese states involved dissociate into the same dissociation channel $Ge(³P)+O(³P).$ Forthe four states, the spectroscopic parameters $(R_e, D_e, ω_e, B_e, ω_eχ_e$ and $T_e)$ have beenobtained, which shows that our results are in very good agreement with the experimentalvalue and other theoretical data at MRCI+Q level. The dipole moments ofthese states are also obtained. In addition, based on the accurate results of spectroscopicconstants at MRCI+Q level, the first 30 vibrational states are determined for thefour low-lying electronic states when $J=0.$ The vibrational levels $G(v)$ and inertial rotationconstants Bv at MRCI+Q level are calculated when $J=0,$ the results of $X¹Σ^+$ and $A¹Π$ states are in concordance with the available other theoretical values and experimentalwork. The dissociation limits, dissociation energies, electronic configurationsat equilibrium internuclear distance for $a'³Σ^+,$ $a³Π$ states also are predicted for the firsttime.
Keywords: GeO molecule; spectroscopic constants; vibrational levels; molecular constants.